Isolation and characterization of Methanosphaera sp. ISO3-F5, a member of a novel and widespread species of rumen methanogens growing with methanol plus hydrogen - Jeyamalar Jeyanathan; Nikola Palevich; Kerri Reilly; Faith P. Palevich; Paul H. Maclean; Dong Li; Eric Altermann; Caroline C. Kim; Inge Maartje van Scheepstal; Simone O. Hoskin; William J. Kelly; Sinead C. Leahy; et al. (The Microbe)
Rumen methanogens predominantly fall into two physiological groups: hydrogenotrophs which use hydrogen (H2) to reduce carbon dioxide (CO2) to methane (CH4), and methylotrophs which use H2 to reduce methanol and methylamines as substrates for methanogenesis. We used a dilution to extinction approach to isolate two hydrogenotrophic Methanocatella spp. and four cultures of methylotrophic methanogens from sheep rumen contents. Three of the methylotrophs were stable mixed cultures containing methanogens belonging to different lineages of the order Methanomassiliicoccales and one was a pure Methanosphaera culture. Methanosphaera sp. ISO3-F5 has a comparatively large genome (2.68 Mb) comprised of two replicons, a chromosome and a megaplasmid. The genome has an average G + C content of 30.5 % and encodes 2360 putative protein-coding genes. Cells of ISO3-F5 have a spherical shape, 0.6–1.2 µm in diameter, usually occurring in pairs or loose clumps, and have no flagellum. Cells stain Gram positive, have a single thick cell wall and divide by the formation of a cross wall. The optimum temperature for growth was 39°C to 42°C and the optimum pH was 6.7–6.8. Acetate was required for growth, but CH4 was not produced from acetate, formate, ethanol, methylamine, or isopropanol with or without H2/CO2. Volatile fatty acids and rumen fluid were also found to enhance the growth of ISO3-F5, while coenzyme M did not. ISO3-F5 produced CH4 from methanol in the presence of H2 and the genes encoding the necessary methanogenesis pathway have been identified. Based on morphological, physiological, and genomic characteristics, ISO3-F5 is a new species of the genus Methanosphaera. Our study shows that simple isolation methods allowed us to culture diverse and significant members of the rumen methanogen community.